2023
DOI: 10.1177/14604582231156476
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and usability of a personalized mHealth app for self-management in the first year following breast cancer surgery

Abstract: This study investigated the feasibility and usability of a personalized mobile health (mHealth) app for self-management during the year following breast cancer surgery. Twenty-nine participants were instructed to use an app and smart band immediately after discharge. Only 18 completed the study. Their perceived necessity and satisfaction for main domains and app were assessed at 1, 2, 4, 6, 9, and 12 months. A self-reporting questionnaire assessed usability at 12 months. Consequently, retention rate as measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This monitoring period will focuse on postoperative recovery and the initial period of treatment. Based on previous research experience, adherence to self-management using a mobile application is expected to decrease after the start of adjuvant treatment in patients with postoperative breast cancer, 13 considering the limited resources of human support.…”
Section: Methods and Designmentioning
confidence: 99%
“…This monitoring period will focuse on postoperative recovery and the initial period of treatment. Based on previous research experience, adherence to self-management using a mobile application is expected to decrease after the start of adjuvant treatment in patients with postoperative breast cancer, 13 considering the limited resources of human support.…”
Section: Methods and Designmentioning
confidence: 99%
“…82.3% said that the app was helpful postoperatively, and 94.1% would recommend it to othersSuggested improvements in anxiety, depression, fatigue and sleep disturbance Lim et al . [46] Single arm 29 recruited but only 18 completed Personalized rehabilitation intervention according to five key criteria: general user information, breast operation type, lymph node surgery type, chemotherapy and hormonal therapy, and change in treatment after surgery. Addition of a connected smart band to act as a step counter, to track heart rate and sleep Assessed at 1, 2, 4, 6, 9, 12 monthsSatisfaction and usability measured after 12 months Reasons given for non-completion as the smart band was uncomfortable (36%), they felt no need for the app (27%), returned to work (18%), difficulty with continuous use because of treatment (9%), and dissatisfaction with exercise (9%) Simon et al .…”
Section: Interventions For Post-surgical Painmentioning
confidence: 99%
“…Lim et al . [46] intervention aimed to support integrated and long-term self-management immediately after surgery and throughout treatments, with the addition of a connected smart band to track steps, heart-rate and sleep. This small study had a high rate of non-completion making it hard to draw conclusions.…”
Section: Interventions For Post-surgical Painmentioning
confidence: 99%
“…Furthermore, it allows for the use of a qualitative approach to illustrate quantitative findings or the integration of various research approaches to provide a thorough and comprehensive picture of the study [ 19 , 20 ]. Previous studies [ 15 , 21 , 22 ] have indicated that interviews and usability questionnaires are prevailing methods used for assessing the usability of mHealth apps. However, there are limited studies regarding the real-time capture of users’ visual interactions and the subsequent retrospective analysis of user engagement with mHealth apps through techniques such as eye tracking.…”
Section: Introductionmentioning
confidence: 99%